Cyber-physical attacks: a growing invisible threat - Loukas, George (Elsevier, BH, 2015)
Front Cover; Cyber-Physical Attacks; Copyright Page; Dedication; Contents; 1 A Cyber-Physical World; Basic Concepts and Definitions of a Cyber-Physical World; Transducers; Controllers; Embedded Systems; Cyber-Physical Systems; The Internet of Things; Defining Cyber-Physical Attacks; Who Should Read This Book; Outline; Chapter 1: A Cyber-Physical World; Chapter 2: A History of Cyber-Physical Security Incidents; Chapter 3: Cyber-Physical Attacks on Implants and Vehicles; Chapter 4: Cyber-Physical Attacks on Industrial Control Systems; Chapter 5: Cyber-Physical Attack Steps. - Chapter 6: Protection Mechanisms and Secure Design PrinciplesChapter 7: Physical-Cyber Attacks; Summary; Follow-Up Questions and Exercises; 2 A History of Cyber-Physical Security Incidents; Reported Incidents by Sector Affected; Energy; Water; Health; Transportation; Defense; A Discussion on the Cyber-Physical Security Incident Reports; Motivations; Second Order Cyber-Physical Dependencies; The Impact of Cyber-Physical Attacks; Summary; Follow-Up Questions and Exercises; 3 Cyber-Physical Attacks on Implants and Vehicles; Implantable Medical Devices; Insulin Pumps. - Implantable Cardioverter DefibrillatorsVehicles; Unmanned Aerial Vehicles; Automobiles; Summary; Follow-Up Questions and Exercises; 4 Cyber-Physical Attacks on Industrial Control Systems; SCADA; SCADA Network Vulnerabilities; Factors Affecting SCADA Security; Strict Real-Time Requirements; Continuous Availability; Misguided Security Perceptions; Commercial-off-the-Shelf Hardware and Software; Interconnectivity; Internet Accessibility; Stuxnet: A Milestone in Industrial Control System Security; The Background; The Payload and the Attack; The Delivery; The Impact and the Aftermath